Intragroup conflict and effectiveness: the moderate role of group emotional intelligence - Antunes, Teresa (2012)
There is a lot of research done about the impact of intragroup conflict on team effectiveness (e.g., Dimas, 2007; Jehn, 1995, 1997; Jehn&Mannix, 2001). However, the results are inconsistent. With our study we intend to contribute for a better understanding of the relationship between intragroup conflict (task conflict and relationship conflict) and team effectiveness (team performance and team satisfaction) by adopting a contingencial approach. The main purpose is to test the role of group emotional intelligence, as we hypothesized that it works as a moderating variable in the relationship between the two variables. To test this hypothesis, we conducted a non-experimental research using a sample of 72 working teams from different functions and organizational contexts. Our results showed that task conflict had a negative impact on both team’s outcomes, while some dimensions of group emotional intelligence had a positive impact on team outcomes. The results also showed an unexpected negative impact of group regulation of members in team performance. Moreover, we found that this dimension of group emotional intelligence moderated the relationship between task conflict and team performance, such as that in teams with high levels in this dimension the effect of task conflict on team performance was positive. Possible explanations of our findings and implications for future research are discussed.